2001
DOI: 10.1002/j.1556-6676.2001.tb01956.x
|View full text |Cite
|
Sign up to set email alerts
|

The Professional Identity of Contributors to the Journal of Counseling & Development: Does It Matter?

Abstract: R. K. Goodyear (2000) criticized the methodology and results of a study which demonstrated that during the editorial terms of Goodyear (1984–1990) and Claiborn (1990–1993) there was a trend toward publishing articles written by psychologists as opposed to counselors in the Journal of Counseling & Development (JCD). The issue of journal content goes to the heart of professional identity. The authors assert that professional affiliation of contributors matters less than the content of the articles published in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
(26 reference statements)
1
22
0
1
Order By: Relevance
“…The extent to which counseling psychology and counseling are the same or different fields is debatable (cf., Goodyear, 2000;Thomas, 1991;Weinrach, Thomas, & Chan, 2001). However, a substantial number of Division 17 members also belong to ACA.…”
mentioning
confidence: 95%
“…The extent to which counseling psychology and counseling are the same or different fields is debatable (cf., Goodyear, 2000;Thomas, 1991;Weinrach, Thomas, & Chan, 2001). However, a substantial number of Division 17 members also belong to ACA.…”
mentioning
confidence: 95%
“…For some time, scholars within the U.S. have debated whether there are differences between counselor educators and counseling psychologists related to research skills and job placement (Goodyear 2000;Weinrach et al 1998;Weinrach et al 2001). In three studies exploring post-graduate occupations, professional behavior, and salary among counselor education and psychology doctoral graduates, Zimpfer (1993Zimpfer ( , 1996 and Zimpfer and DeTrude 1990 found that across most outcomes (i.e., salary, professional activities, and future goals) counselor education and counseling psychology graduates were more similar than different.…”
Section: Extant Literaturementioning
confidence: 99%
“…Research that examines professional identity for counselors in the U.S., and its perceived association with terminal degrees, has received some attention in the literature (Goodyear 2000;Weinrach et al 1998;Weinrach et al 2001), yet little research has explored the actual process of doctoral education in general (Haworth and Bair 2000) and in counselor education specifically (Zimpfer et al 1997). Moreover, there is no information in the counseling literature about how doctoral programs within and outside the United States individually tailor their degree process.…”
mentioning
confidence: 96%
“…Professional identity has been defined as the possession of a core set of values, beliefs, and assumptions about the distinctive characteristics of one's selected career that differentiates it from other careers (Weinrach, Thomas, & Chan, 2001). Identity formation is influenced by the importance and connection that individuals attach to their background and how they interpret their experiences.…”
Section: Sotl Identity Formation: Differences Among Faculty Staff Amentioning
confidence: 99%